2013
DOI: 10.1016/j.bpj.2013.03.066
|View full text |Cite
|
Sign up to set email alerts
|

New Organelles by Gene Duplication in a Biophysical Model of Eukaryote Endomembrane Evolution

Abstract: Extant eukaryotic cells have a dynamic traffic network that consists of diverse membrane-bound organelles exchanging matter via vesicles. This endomembrane system arose and diversified during a period characterized by massive expansions of gene families involved in trafficking after the acquisition of a mitochondrial endosymbiont by a prokaryotic host cell >1.8 billion years ago. Here we investigate the mechanistic link between gene duplication and the emergence of new nonendosymbiotic organelles, using a mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…The strongest evidence in favor of this mechanism was the observation that, whereas many of the organelle-specific subfamilies of SNAREs, Rabs, and Adaptins had duplicated pre-LECA, a few of the paralogs associated with endocytic organelles had emerged in lineage-specific fashion independently, but with parallel functions implying a general process for organelle evolution acting on the system . Recent computer simulations have confirmed that such a mechanism could indeed produce an organelle-generating mechanism based on purely theoretical calculations of protein -protein interactions and the evolution of specificity within paralogs (Ramadas and Thattai 2013).…”
Section: A Sophisticated Ancient Membrane-trafficking Machinery and Amentioning
confidence: 99%
“…The strongest evidence in favor of this mechanism was the observation that, whereas many of the organelle-specific subfamilies of SNAREs, Rabs, and Adaptins had duplicated pre-LECA, a few of the paralogs associated with endocytic organelles had emerged in lineage-specific fashion independently, but with parallel functions implying a general process for organelle evolution acting on the system . Recent computer simulations have confirmed that such a mechanism could indeed produce an organelle-generating mechanism based on purely theoretical calculations of protein -protein interactions and the evolution of specificity within paralogs (Ramadas and Thattai 2013).…”
Section: A Sophisticated Ancient Membrane-trafficking Machinery and Amentioning
confidence: 99%
“…eukaryote evolution | mitochondria | vesicles | dynamin | FtsZ E ukaryotes arose through the acquisition of mitochondria by an archaeal host cell about 2 billion y ago (1,2), a watershed moment in the evolution of the modern compartmentalized cell plan (3). A second transformative endosymbiotic event, the acquisition of a cyanobacterium by a eukaryotic host to form chloroplasts, gave rise to the photosynthetic eukaryotic lineages (4).…”
mentioning
confidence: 99%
“…Models that focus on size distributions allow for a continuum of structures from transport vesicles to large compartments, and account for fission and fusion of all such structures [26]. Many models focus on compartments and the complex rules of molecular specificity, but do not treat transport vesicles explicitly and do not account for inter-vesicle fusion [25], [28], [29]. In such models, compartment compositions are specified by the concentrations of various molecules, and vesicle traffic is represented by a series of ordinary differential equations.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, mathematical modeling has proved useful in connecting basic molecular events, such as budding and fusion, to dynamic processes, such as cargo transport, and finally to the compartmental compositions of the endomembrane system [25], [26], [27], [28], [29], [30]. These models require the specification of a large number of parameters.…”
Section: Introductionmentioning
confidence: 99%